Cyrene as a Bio-Based Solvent for the Suzuki–Miyaura Cross-Coupling - Wilson, Kirsty L.; Murray, Jane; Jamieson, Craig; Watson, Allan J. B. (Synlett, 2018)
The Suzuki–Miyaura (SM) cross-coupling is the most broadly utilized Pd-catalyzed C–C bond-forming reaction in the chemical industry. A large proportion of SM couplings employ dipolar aprotic solvents; however, current sustainability initiatives and increasingly stringent regulations advocate the use of alternatives that exhibit more desirable properties. Here we describe the scope and utility of the bio-derived solvent Cyrene™ in SM cross-couplings and evaluate its suitability as a reaction medium for this benchmark transformation from discovery to gram scale.
Keywords: boron; cross-coupling; green chemistry; palladium; solvents